Application of Urine-Derived Stem Cells to Cellular Modeling in Neuromuscular and Neurodegenerative Diseases - Sato, Mitsuto; Takizawa, Hotake; Nakamura, Akinori; Turner, Bradley J.; Shabanpoor, Fazel; Aoki, Yoshitsugu (Frontiers in Molecular Neuroscience, 2019)
Neuromuscular and neurodegenerative diseases are mostly modelled using genetically modified animals such as mice. However, animal models do not recapitulate all the phenotypes that are specific to human disease. This is mainly due to the genetic, anatomical and physiological difference in the neuromuscular systems of animals and human. The emergence of direct and indirect human somatic cell reprogramming technologies may overcome this limitation because they enable the use of disease and patient-specific cellular models as enhanced platforms for drug discovery and autologous cell-based therapy. Induced pluripotent stem cells (iPSCs) and urine-derived stem cells (USCs) are increasingly employed to recapitulate the pathophysiology of various human diseases. Recent cell-based modelling approaches utilizes highly complex differentiation systems that faithfully mimic human tissue- and organ-level dysfunctions. In this review, we discuss promising cellular models, such as USC- and iPSC-based approaches, that are currently being used to model human neuromuscular and neurodegenerative diseases.